Ontology model for intake suggestion and preparation for malay confinement dietary recipes - M. Hamiz; Haryani Haron; M. Bakri; Nur Liyana Mohd Lazim (Institute of Advanced Engineering and Science, 2020)
This paper presents the ontology model for Malay Confinement Dietary (MCD) recipes which include the intake suggestion and its preparation. MCD plays a big role to ensure that mothers in confinement get the right nutrient in order to restore back their health. In the current research on MCD, the covered part is only on what are the foods allowed to be taken by mothers during confinement and the nutrients that it can boost in mothers’ body. However, it does not include what are the preparation methods of the food and what is the suggested intake time for that dish. These two aspects could give the certainty factor for mothers to get the sufficient nutrient during confinement. But those knowledges are known by the traditional Malay midwives. Hence, this tacit knowledge should be modeled into an ontology model as one of the knowledge preservation methods. Three new classes together with four new object properties were added to the current model and based on testing that has been done, the extended new model of ontology could retrieve the correct information as needed.